2018
DOI: 10.1093/pubmed/fdy165
|View full text |Cite
|
Sign up to set email alerts
|

Improving health equity for ethnic minority women in Thai Nguyen, Vietnam: qualitative results from an mHealth intervention targeting maternal and infant health service access

Abstract: The mMom project demonstrated the acceptability of mHealth in a remote Vietnamese region with a high proportion of disadvantaged EMW. The messages promoted increased contact between participants and health providers, which holds potential to address the marginalization of EMW from the health system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 25 publications
0
36
0
1
Order By: Relevance
“…The text messages sent via the mMOM platform addressed some of these vulnerabilities. 8 In Peru, given that husbands did not attend prenatal check-ups due to work obligations, women reported appreciating accessing and sharing information from trusted sources such as health providers through the Internet with their partners. 9…”
Section: Seizing Digital Health Opportunities To Transform Gender Inementioning
confidence: 99%
See 1 more Smart Citation
“…The text messages sent via the mMOM platform addressed some of these vulnerabilities. 8 In Peru, given that husbands did not attend prenatal check-ups due to work obligations, women reported appreciating accessing and sharing information from trusted sources such as health providers through the Internet with their partners. 9…”
Section: Seizing Digital Health Opportunities To Transform Gender Inementioning
confidence: 99%
“…Being more informed and confident also improved their interactions and relationships with health providers. 8 Future research should ideally explore intersectionality between gender, ethnicity, age, parity and marital status, among a range of contextually relevant social markers, for the women and family members involved in the project.…”
Section: Seizing Digital Health Opportunities To Transform Gender Inementioning
confidence: 99%
“…In Vietnam, McBride et al 17 piloted a low-cost mhealth intervention among ethnic minority women who experience disproportionately high incidence of infant and maternal mortality and suffer from other forms of exclusion. The researchers addressed local language needs and provided information about maternal and child health via SMS and their community healthcare workers.…”
Section: Theme 1: Digital Health Can Positively Influence Health Equitymentioning
confidence: 99%
“…The range of tools for CHWs involved in these studies include job aids, scheduling systems, checklists and/or client education and behavior change communication tools. However, of the eight studies conducted in both Asia and sub-Saharan Africa, only two of them sought beneficiary perceptions of the interventions and how it influenced the uptake of services among beneficiaries [12][13][14][15][16][17][18][19]. In studies where beneficiaries' perspectives were sought, they reported better quality of interactions with CHWs, active participation in care-seeking, and better quality of services [14,16].…”
Section: Introductionmentioning
confidence: 99%